Two-phase contact Stefan problem - Borodin, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The existence of the classical solution of the many-dimensional two-phase Stefan problem is proved for any finite time interval in the case of contact of an unknown (free) boundary with the known one.